Recent progress and scientific challenges in multi-material additive manufacturing via laser-based powder bed fusion - Wei, Chao; Li, Lin (Virtual and physical prototyping, 2021)
Multi-material additive manufacturing provides a new route for fabricating components with tailored physical properties. Laser-based powder bed fusion (L-PBF), also known as selective laser melting, is a powder bed-based additive manufacturing technology. This technology affords the advantage of manufacturing metallic and non-metallic materials with high geometrical resolution. An emerging field relevant to the foregoing is multi-material L-PBF. This paper reviews the latest progress in this field including multiple material powder deposition mechanisms, molten pool behaviour, process characteristics of printing metal-metal, metal-ceramic, and metal-polymer multiple material components, and potential applications. Finally, scientific and technological challenges are presented.